2015
DOI: 10.1039/c4sc01592d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism, reactivity, and selectivity of the iridium-catalyzed C(sp3)–H borylation of chlorosilanes

Abstract: DFT calculations are used to elucidate the reaction mechanism, the role of the chlorosilyl group, and primary vs. secondary and C(sp3)–H vs. C(sp2)–H selectivity of the iridium-catalyzed borylation of chlorosilanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
50
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 113 publications
(60 reference statements)
13
50
0
2
Order By: Relevance
“…This reaction was shown to be facile in the recently reported Ir-catalyzed C(sp 3 ) H borylation of chlorosilane. 116 A recent DFT study reported that the reaction occurs via oxidative addition of the C(sp 3 )H bond to the iridium(III) triboryl complex followed by the reductive elimination of borylated product, 117 which is essentially the same as the mechanism of Ir-catalyzed borylation of benzene. Also, the C(sp Another important development is to achieve regioselective CH σ-bond activation in these direct borylation reactions, which is also an important target in the chemistry of CH activation because regioselective CH σ-bond activation is not easy.…”
Section: Catalyses For Hydrosilylation Of Alkenementioning
confidence: 91%
See 1 more Smart Citation
“…This reaction was shown to be facile in the recently reported Ir-catalyzed C(sp 3 ) H borylation of chlorosilane. 116 A recent DFT study reported that the reaction occurs via oxidative addition of the C(sp 3 )H bond to the iridium(III) triboryl complex followed by the reductive elimination of borylated product, 117 which is essentially the same as the mechanism of Ir-catalyzed borylation of benzene. Also, the C(sp Another important development is to achieve regioselective CH σ-bond activation in these direct borylation reactions, which is also an important target in the chemistry of CH activation because regioselective CH σ-bond activation is not easy.…”
Section: Catalyses For Hydrosilylation Of Alkenementioning
confidence: 91%
“…The factors for controlling regioselectivity have been discussed in theoretical work of borylation of substituted arenes, heterocycles, 119 and chlorosilane. 117 In the direct borylation of alkylamines and alkylethers, the regioselectivity has been experimentally and theoretically well investigated. 118 I wish to skip the discussion to save the space.…”
Section: Catalyses For Hydrosilylation Of Alkenementioning
confidence: 99%
“…In this paper, we investigate all proposed mechanisms for both the S and R substrates on an equal footing. We have used the quantum mechanical (QM) cluster approach, which has extensively been used to study catalytic mechanisms and structures of enzymes [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] . In this approach, the most important residues are cut out from the active site of the enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…7 While this reaction was initially proposed to proceed through aldehyde/ allene oxidative cyclization on rhodium(I), computational studies by Himo and co-workers later indicated that oxidative cyclization of two allene molecules is more likely to operate, forming the C−C bond between the central allenic carbons (see the box in Scheme 1a). 8 In pursuit of our continuing 51 interest in low-valent cobalt catalysis 9 for hydroacylation 10,11 52 and allene transformations, 12−14 we have found that a cobalt catalyst promotes the aldehyde/allene 1:2 coupling in a mol %) in toluene at 40 °C to afford 3aa in 97% yield with t1 79 regioselectivity higher than 20:1 (Table 1, entry 1). A 80 comparable catalytic activity was achieved using CoBr 2 or 81 Co(acac) 3 as the precatalyst (Table 1, entries 2 and 4), 82 whereas the reaction became rather sluggish with CoCl 2 83 (Table 1, entry 3).…”
mentioning
confidence: 99%